Evaluation under grazing of pasture germplasm in advanced stages of selection - Jones, Raymond J. (International Center for Tropical Agriculture, 1993)
Evaluation under grazing is an important stage in the evaluation of pasture germplasm for the selection of potential new cultivars. Entry to this stage of evaluation presupposes an already existing adaptation to the climatic and edaphic conditions of the relevant area or areas, high yield, resistance to pests and diseases, and a clear-cut objective for the eventual use of the germplasm under evaluation. Common grazing of all accessions under evaluation is usual at this stage but care needs to be taken to avoid bias. Suggestions for avoiding bias include grouping accessions of similar plant form and including them in separate experiments, the separation of fertilizer treatment variables, the use of two or more grazing regimes, and the use of individually grazed plots. Practical problems concerning number of sites, strategies to use, duration of experiments, and pasture measurements are discussed.